PREDICATIVE VALUE OF SOME COMMON MOBILITY TESTS CRUCIAL FOR FORMING MARK IN THE PHYiCAL EDUCATION TEACHING - Danijela Bulatović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Up to the sam ple of 86 stu dents from 5th class of Ele men tary School »Ok to ih« in Pod go ri ca, we ma de re se arch in or der to esta blish the le vel of sta ti sti cal im por tan ce of the com mon mo bi lity tests in fl u en ce for for ming of the physi cal edu ca tion mark. By using of Pir son cor re la ti ve analysis, fol lo wed by the re gres si ve analysis, it was esta blis hed the im por tant mu tual con nec tion bet we en pre di ca ti ve and cri te rion va ri a ble. The co ef fi ci ent of cor re la tion has been spread from the mid dle (MT600= . 488), to the high nu me ri cal va lu es (MSDM =. 735).